Enchondroma in Flat Bone: a Rare Case Report - Ferdous, Sharmin; Nafisa, Jahan; Jahan, Nushrat; -, Md Nadiruzzaman (Bangladesh Journal of Nuclear Medicine, 2018)
Enchondroma represents a common bone tumor of the hand. The flat bone is a rare location. We report a case of flat bone (rib) enchondroma presenting as swelling in her right lower chest. The diagnosis is suggested by radiological study and then confirmed by histological study after biopsy. The clinical and radiological aspects of this rare condition are discussed. Bangladesh J. Nuclear Med. 19(2): 155-156, July 2016